Meta-analysis of effect of single versus dual antiplatelet therapy on early patency of bypass conduits after coronary artery bypass grafting - Nocerino, Angelica G.; Achenbach, Stephan; Taylor, Allen J. (American Journal of Cardiology, 2013)
Aspirin monotherapy represents a standard therapy for preserving patency after coronary artery bypass grafting. Randomized trials addressing whether dual antiplatelet therapy is superior to single antiplatelet therapy to achieve graft patency early after coronary surgery have shown inconsistent results. We performed a meta-analysis of randomized controlled trials comparing single versus dual antiplatelet therapy after coronary artery bypass grafting. In a systematic published works search, 5 randomized controlled trials meeting inclusion criteria were identified. Pooled efficacy and safety data were abstracted and analyzed using a fixed-effects model. The 5 trials included 958 patients and a total of 2,919 grafts with treatment up to 1 year after coronary bypass surgery. Early occlusion was identified in 165 (6.5%) of 2,526 bypass grafts. Early occlusion occurred in a greater proportion of grafts among patients treated with single therapy (105 of 1,369; 7.7%) compared with dual antiplatelet therapy (69 of 1,386; 5.0%; p = 0.005). The odds ratio for graft occlusion with single versus dual therapy was 1.59 (95% confidence interval 1.16 to 2.17). For vein grafts, single antiplatelet therapy was associated with a significantly increased graft loss rate (91 of 846; 10.8%) versus dual antiplatelet therapy (57 of 860; 6.6%; odds ratio 1.70 [1.20 to 2.40]; p = 0.003). There was no effect on arterial graft patency. Bleeding was noted in 3.3% and 4.9% of single and dual therapy treated patients, respectively, with only 3 trials reporting bleeding outcomes. In conclusion, among 958 patients randomly assigned to either single or dual antiplatelet therapy for up to 1 year after coronary bypass surgery, single antiplatelet therapy significantly increased the risk for graft occlusion, an effect isolated to vein grafts, not arterial grafts. © 2013 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08